Analisis Resepsi Informasi Kesehatan Mental pada Akun YouTube Satu Persen - Atmaditia, Syafa Shaquilla Zuhayr (Universitas Muhammdiyah Yogyakarta, 2025)
YouTube is a media platform that bridges information related to physical and mental health. Through the contribution of the millennial generation, there is an educational YouTube channel that is interesting to research, namely Satu Persen Indonesian Life School. Based on that, this research aims to see how far the message interpreted by the Satu Persen YouTube channel audience in understanding mental health information through various personal perspectives. Researchers use Hall's reception theory based on three categories of positions (Dominant Hegemonic, Negotiated, Oppositional). Researchers used a descriptive qualitative approach with data collection methods through online interviews with five informants. From the overall data obtained, the Dominant-Hegemonic Position is the majority form of reception from the form of reception of informants I-II-III-V with the identification of the Satu Persen YouTube channel as an account that knows the factors and indicators that support mental health conditions from good to bad. Meanwhile, Negotiated Position is a form of reception for informant IV regarding everyone’s differentiated questions in digesting Mental Health information through Satu Persen content. Remaining zero Oppositional Position reception was found by informants because of their openness in receiving and digesting information from Satu Persen YouTube channel content.